Coinfection by Babesia spp. and Anaplasma platys in domestic canine, case report - Ferraz, Alexsander (2020)
Hemoparasitosis are frequent disorders in the routine of the Veterinary Clinic. Among the main etiological agents, the Babesia and Anaplasma genres stand out, which parasitize erythrocytes and platelets, respectively. The main form of transmission of both parasites is through the tick Rhipicephalus sanguineus. Clinical signs are usually nonspecific, and include fever, apathy, anorexia and hematological changes, such as anemia and thrombocytopenia, which can make detection even more difficult. Thus, the performance of complementary exams is extremely important for the definitive diagnosis of the agent. The objective of this work was to describe the report of a dog, coinfected by Babesia spp. and Anaplasma platys, showing the diagnosis and treatment of these diseases.